CARING NATIONAL IDENTITY THROUGH TEACHER CONTRIBUTIONS IN THE BORDER: PANCASILA ACTIONISTIC BASIC IMPLEMENTATION - Jagad Aditya Dewantara; Efriani Efriani; sulistyarini sulistyarini (Universitas Pahlawan Tuanku Tambusai, 2020)
This study looks at the phenomenon of Nationalism Education in various tribes in the Entikong region of Indonesia which borders Malaysia. The purpose of this study looks at the contribution of teachers in the scope of nationalization directly and factually, this nationalization is closely related to the implementation of the Pancasila axillary values as forming national identity. This research is focused on students and the practice of teachers who live in border areas. Retrieval of field data using descriptive qualitative methods using research designs and semi-ethnographic research procedures. The results of the field research indicate that the teacher carries out nationalization practices and campaigns through learning integration in the classroom and outside the classroom. There are 6 contributions seen in this study: teachers as instructors, teachers as managers, teachers as mentors, teachers as evaluators, teachers as members of professional organizations, and teachers as public relations specialists. This implication is expected to be able to strengthen the basis of national identity, especially in instilling Panacasila axiological values aimed at students at the Entikong border